1991
DOI: 10.1007/bf00166299
|View full text |Cite
|
Sign up to set email alerts
|

PERG and spectral sensitivity in ocular hypertensive and chronic open-angle glaucoma patients

Abstract: Pattern electroretrinography (PERG) was performed in 33 patients with chronic open-angle glaucoma (COAG), 18 ocular hypertensive (OH) patients, and 24 normal subjects. COAG patients exhibited significantly lower PERG amplitudes than did normal subjects (P8rps = 0.025; P16rps less than 0.0001). The OH patients fell into two distinct groups: those with normal PERG scores and those with lower than normal scores. OH patients with PERG scores significantly lower than control values demonstrated significantly larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Especially in early diagnosis of glaucoma it seems to be useful because amplitude reduction can indicate early glaucomatous damage [1,5,9,10,25,26,29,36,38,42,43,44]. However, this patient group covers an age range where retinal contrast is impaired by factors like media opacity, subop-timal accomodation, and small pupil size [20,22,33,34,39].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in early diagnosis of glaucoma it seems to be useful because amplitude reduction can indicate early glaucomatous damage [1,5,9,10,25,26,29,36,38,42,43,44]. However, this patient group covers an age range where retinal contrast is impaired by factors like media opacity, subop-timal accomodation, and small pupil size [20,22,33,34,39].…”
Section: Introductionmentioning
confidence: 99%
“…PERG is altered in glaucoma and in many cases of OHT, 9 even if in some case with OHT PERG may be normal. 10 Several authors in human studies found PERG as a predictive value to identify those patients with elevated IOP who develop a glaucoma before visual field changes occur. 11,12 PERG has higher sensibility to detect glaucomatous changes 12,13 and it is abnormal in most patients with manifest disease.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] The general pattern is that BYP defects, although similar in location and shape, appear earlier and are larger than SAP defects. [ 10 11 12 13 ]…”
mentioning
confidence: 99%